Comparative study on direct and indirect bracket bonding techniques regarding time length and bracket detachment - Bozelli,Jefferson Vinicius (2013)
OBJECTIVE: The aim of this study was to assess the time spent for direct (DBB - direct bracket bonding) and indirect (IBB - indirect bracket bonding) bracket bonding techniques. The time length of laboratorial (IBB) and clinical steps (DBB and IBB) as well as the prevalence of loose bracket after a 24-week follow-up were evaluated. METHODS: Seventeen patients (7 men and 10 women) with a mean age of 21 years, requiring orthodontic treatment were selected for this study. A total of 304 brackets were used (151 DBB and 153 IBB). The same bracket type and bonding material were used in both groups. Data were submitted to statistical analysis by Wilcoxon non-parametric test at 5% level of significance. RESULTS: Considering the total time length, the IBB technique was more time-consuming than the DBB (p < 0.001). However, considering only the clinical phase, the IBB took less time than the DBB (p < 0.001). There was no significant difference (p = 0.910) for the time spent during laboratorial positioning of the brackets and clinical session for IBB in comparison to the clinical procedure for DBB. Additionally, no difference was found as for the prevalence of loose bracket between both groups. CONCLUSION: the IBB can be suggested as a valid clinical procedure since the clinical session was faster and the total time spent for laboratorial positioning of the brackets and clinical procedure was similar to that of DBB. In addition, both approaches resulted in similar frequency of loose bracket.